Treatment at the end of life in patients with advanced melanoma$amulticenter DeCOG study of 1067 patients from the prospective skin cancer registry ADOReg - Forschner, Andrea Lydia; Kähler, Katharina C.; Gschnell, Martin; Langan, Ewan A.; Weishaupt, Carsten; Meiss, Frank; Thoms, Kai-Martin; Wahl, Renate U.; Göppner, Daniela; Garzarolli, Marlene; Sachse, Michael; Schlaak, Max; et al. (Frontiers in immunology, 2025)
BackgroundAlthough systemic therapies have improved considerably over the last decade, up to 50% of patients with metastatic melanoma still die due to disease progression. Oncological treatment at the end-of-life phase is challenging. The aim of this study was to investigate the frequency and type of systemic therapy received by melanoma patients in their end-of-life phase.MethodsPatients with metastatic melanoma who had died between January 1, 2018 and October 31, 2022 were identified from the prospective multicenter skin cancer registry ADOReg. Study endpoints were percentage of patients who had been treated with systemic therapy within the last three months of life, timepoint of initiation of the last-line therapy, overall survival, treatment benefit and the incidence of treatment-related adverse events.ResultsIn total, 1067 patients from 46 skin cancer centers were included. Most of the patients (63%) had received immune checkpoint inhibitors (ICI) as last-line therapy, 22% targeted therapies (TT) and 12% chemotherapy (CTX). Comparing last-line ICI and TT, patients with TT were significantly more likely to benefit from treatment and had significantly fewer and milder treatment-related AE than patients with ICI. Even though two thirds of patients had received ICI as a last-line therapy, the majority of these patients (61%) had stopped therapy within the last 30 days of life, whereas the majority of patients with TT (66%) still continued their treatment to the end of life. We found markedly fewer patients with initiation of ICI within 30 days before their death (19%) compared to a historic cohort including patients who died in 2016 or 2017 (39%).ConclusionTreatment approaches near the end of life have markedly changed in skin cancer centers in Germany over recent years, with ICI prescribed less frequently in the end-of-life phase. In contrast, TT are frequently administered, even within the last 30 days of life. It should also be considered that discontinuation of TT can result in rapid tumor progression. Due to the oral administration and a low rate of severe toxicity, TT appear to be a suitable treatment option, even in the end-of-life situation of melanoma patients.
Gesehen am 10.07.2025